Influence of Land Reclamation on Fresh Groundwater Lenses in Oceanic Islands: Laboratory and Numerical Validation. Issue 10 (4th October 2021) - Sheng, Chong; Jiao, Jiu Jimmy; Xu, Hehua; Liu, Yi; Luo, Xin
Abstract: Fresh groundwater lenses in tropic oceanic islands are important freshwater resources for local inhabitants and ecosystems. These reef‐carbonate islands typically have a dual‐aquifer structure, with poorly consolidated Holocene sediments deposited unconformably on Pleistocene limestone reef deposits. Land reclamation has been carried out on the reef flats or shallow water areas in coral islands, a very common practice in the Indian Ocean and the South China Sea. However, there is a lack of comprehensive understanding of how the groundwater system will respond to land reclamation. In this study, the impact of land reclamation on the fresh groundwater lens in an island is investigated using multiple methods: sand‐tank experiments, sharp‐interface analytical solutions, and numerical modeling. This study demonstrates that land reclamation can increase the freshwater storage of the lens and shift the water divide toward the reclamation area. Furthermore, a lower permeability fill material especially with a greater scale or thickness leads to higher freshwater storage. However, the expansion of the lens will be truncated due to the high‐permeability of the lower layer. These observations and findings from the laboratory experiments and two‐dimensional numerical simulations are further ground‐truthed by the three‐dimensional modeling of Yongxing Island in the South China Sea. The findings of this study provide a comprehensive understanding of the impact of land reclamation on island groundwater system and the theoretical supports for Small Island Developing States to use the reclamation not only for urban development but also for extra aquifer to enhance the water resource sustainability under the climate change. Plain Language Summary: Groundwater on oceanic islands in the form of fresh groundwater lenses (FGL) that serve as an important freshwater resource for human consumption and ecosystem services. With intensifying sea‐level rise and global warming, many oceanic islands are shrinking, which leads to the decreasing or even disappearance of the FGL. Land reclamation seems to be the best choice to provide not only valuable land for urban development, but also extra aquifer space for the storage of freshwater resources. In this research, we evaluated the impacts of land reclamation on FGL by using multiple methods: laboratory sand‐tank experiments, analytical solutions, and numerical modeling. Our results show that land reclamation can increase the freshwater storage of the lens and reshape the groundwater system in oceanic islands. Furthermore, a lower permeability fill material especially with a greater scale or thickness leads to higher freshwater storage. However, the expansion of the lens will be truncated due to the high‐permeability of the lower layer on tropical coral islands. Finally, these findings above are also further ground‐truthed by the three‐dimensional modeling of Yongxing Island. Overall, the findings of this work have important global implications for water resources management especially for the Small Island Developing States. Key Points: The impact of land reclamation on the fresh groundwater lens in island was investigated by laboratory, analytical and numerical methods Land reclamation increases the fresh groundwater storage and reshapes the groundwater system in the oceanic island The response of the fresh groundwater lens to land reclamation in islands is subject to the oceanic aquifer structure